2008
DOI: 10.1016/j.jaad.2008.07.018
|View full text |Cite
|
Sign up to set email alerts
|

A gene signature of nonhealing venous ulcers: Potential diagnostic markers

Abstract: Background Venous leg ulcers are responsible for more than half of all lower extremity ulcerations. Significant interest has been focused on understanding the physiologic basis upon which patients fail to heal with standard therapy. Objective This study uses complementary DNA microarray analysis of tissue samples from healing and non-healing venous leg ulcers to identify the genetic expression profiles from these dichotomous populations. Methods Ulcer size and chronicity, factors that have been identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 38 publications
2
61
1
Order By: Relevance
“…Recent studies on complementary DNA-microarray have demonstrated diversity in genetic expression of healing vs nonhealing wounds. 7 An altered expression was found in genes that code for structural factors, mediators of inflammation and apoptotic pathways. The authors demonstrated that healing and nonhealing leg ulcers are characterized by a completely different genetic physiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies on complementary DNA-microarray have demonstrated diversity in genetic expression of healing vs nonhealing wounds. 7 An altered expression was found in genes that code for structural factors, mediators of inflammation and apoptotic pathways. The authors demonstrated that healing and nonhealing leg ulcers are characterized by a completely different genetic physiology.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent paper comparing healing vs nonhealing lesion expression profiles found that none of the assumed genes involved in wound repair (ie, platelet-derived growth factors [PDGF] or keratinocyte growth factor [KGF]) were significantly downregulated in nonhealing ulcers. 7 In recent years, hypothetical molecular mechanisms have been suggested, by means of which local iron overload facilitates the development of VLU. This model has been compared to other iron-driven lesions in neurodegenerative disorders.…”
mentioning
confidence: 99%
“…If the genetic contribution to proper palatogenesis is unquestionable, and the list of genes involved in cleft lip and palate established at about 300 (Jugessur et al, 2009), it has been challenging to generate a workable list of genes involved in wound healing, mainly because of the complexity of the process and the difficulties of obtaining relevant human samples. Nevertheless, a few studies have performed gene expression profiling of cutaneous wound healing (Deonarine et al, 2007; Roupe et al, 2010; Nuutila et al, 2012), or identified a genetic signature unique to non-healing wounds (Charles et al, 2008), yet none provided access to the full list of differentially-regulated genes. Using available information from these studies, we estimated the percentage of reported wound-healing genes that shared a role in CL/P.…”
Section: When Things Go Wrongmentioning
confidence: 99%
“…The importance of this fibrous protein in biological processes, and in particular in the healing wound, has been highlighted through work demonstrating keratin plays a crucial role in healing (7), and additionally as an indicator in chronic wounds where down regulation of keratins has been associated with poor healing (8). The use of exogenous keratin protein in the treatment of tissue injuries has been the subject of extensive research with positive healing responses found in the areas of topical wound care (9), orthopaedic implants (10) and nerve regeneration (11).…”
Section: Introductionmentioning
confidence: 99%